Analisis Jumlah dan Distribusi Ground Control Point Yang Efektif dan Efisien Pada Pemetaan Foto Udara: Studi Kasus di Desa Kohong, Kecamatan Barito Tuhup Raya, Kabupaten Murung Raya, Provinsi Kalimantan Tengah - Hangger Aqiim Mohammad Pandego; Fajrin Fajrin; Dwi Arini (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Aerial photo mapping requires Control Points (CP). The Indonesian National Standard 8202:2019 regulates the number of CPs needed. The smallest area regulated is less than 250 km². Projects with an area of less than 1 km² have the same number of CPs as those with an area of less than 250 km². This is neither effective nor efficient because the CP work depends on the number of workers and requires time based on access to the project site. This study aims to identify the minimum number of CPs and the appropriate distribution of CPs for aerial photo mapping at a scale of 1:2,500 class 1 that is effective and efficient in terms of time and cost. The study uses seven schemes. Schemes 1 and 7 use 4 Ground Control Points (GCP) and 5 Independent Control Points (ICP). Scheme 2 uses 5 GCPs and 4 ICPs. Schemes 3, 4, 5, and 6 use 3 GCPs and 6 ICPs. Each scheme will be evaluated based on CE90 and LE90 values. The maximum CE90 value is 0.75 m, and the LE90 value is 0.5 m. The effective and efficient scheme in terms of time and cost is determined by the number of GCPs used, as well as the CE90 and LE90 values. The results indicate that all schemes have CE90 and LE90 values below the maximum standard. Scheme 4 is identified as the most effective due to having the highest CE90 and LE90 values among the schemes, with CE90 at 0.028 m and LE90 at 0.448 m. Scheme 4 is also identified as the most efficient because it uses a minimal number of GCPs—only three—distributed diagonally from the Southeast to the Northwest in the project area.